Corporate social responsibility and the role of rural women in strengthening agriculture-tourism linkages in Nigeria's oil producing communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Vincent A. Onodugo; Justitia Odinakachukwu Nnabuko; Babatunde A. Adedibu (African Governance and Development Institute (AGDI), 2020)
This paper extends and contributes to the literature on tourism for transformative and inclusive growth from the corporate social responsibility (CSR) perspective. Specifically, we examine the impact of CSR of multinational oil companies (MOCs) on empowerment of rural women in strengthening agriculture-tourism linkages in Niger Delta region of Nigeria. A total of 800 rural women were sampled across the region. Results from the use of a logit model indicates that rural women seldom participate in the global memorandum of understandings (GMoUs) interventions in agritourism value chain projects, due to the norms and culture of the rural communities. This implies that if the tradition of the people continues to hinder direct participation of the rural women from GMoUs programmes, achieving gender equality and cultural change would be limited in the region, and rural women would remain excluded from the economic benefits of agritourism when compared with the male counterparts. The finding suggests that, GMoU interventions engaging women smallholders in the tourism value chain can be an important vehicle for advancing gender empowerment and fostering social inclusion. Also, cluster development boards (CDBs) should pay close attention to which extent the participation of rural women in the GMoUs projects may be limited by traditions.
Keywords: 330; Agriculture-tourism linkages; corporate social responsibility; multinational oil companies; young rural women; sub-Saharan Africa